THE SOUND CHANGE OF ADDING MORPHEME IN THE WORD ‘THERE’ AND ‘WHERE’ IN CAMBRIDGE ADVANCED LEARNER’S DICTIONARY (THIRD EDITION): A PHONOLOGY STUDY - Nurfithri, M.Hum (Jurnal Sastra - Studi Ilmiah Sastra, 2019)
This research is aimed to identify the sound change of adding morpheme in the word„there‟ and „where‟. It is showed by analyzing the base words that create new words and the sound change in creating new words. This study was conducted by qualitative descriptive method to describe and analyze the data. The data of this research are taken from cambridge advanced learner‟s dictionary (third edition). The result of the analysis showed that the word there and where are attached by another morpheme. The word there is attached by about, after, by, fore, in and of. The conclusion of those attaching in phonetic transcription is that if the word there is attached by the morpheme that begins with vocal, the sound vocal in the beginning is moved being unite with the sound rand if the word there is attached by the morpheme that begins with consonant, the sound r in the middle (in base, it is the end) is lost or unsound. It is also happened in the word„where‟ that is attached by about, as, by, fore, in, over, upon and ever.